Pengaruh Gender, Lingkungan Kerja, dan Kompensasi terhadap Kinerja Karyawan di PT Kamaltex - Wulandari, Dika Kurnia; Wijayanto, Petrus (Jurnal Maksipreneur, 2024)
Human resources are crucial aspect of a company. A comfortable work environment means employees will work optimally. If employees do their work well, then high efficiency, effectiveness, and quality can be achieved in the company. This research aims to examine the effect of gender, work environment, and compensation on employee performance at PT Kamaltex.  The research results show that compensation has a positive effect on employee performance, also that the work environment has a positive effect on employee performance, which means that the better the compensation and work environment of a company will provide a significant increase in employee performance.